Research progress on trace elements-modified titanium implant surfaces - CAO Zhiwei (口腔疾病防治, 2020)
Traditional titanium implants are bioinert, and some biological properties, such as osteogenic and antibacterial properties, can be obtained by adding different trace elements to their surfaces. These trace elements can help enhance implant-bone binding and effectively prevent peri-implantitis. Different trace elements have different advantages, and different modification methods can also affect the biological properties. In this paper, the biological properties of titanium implant surfaces modified by trace elements were reviewed. The results of a literature review show that implant surfaces modified by fluoride, silver, zinc, manganese, etc. can inhibit the growth of bacteria and reduce the negative impact on normal cells from bacteria. Other elements, such as strontium, tantalum and cobalt, can promote the differentiation of osteoblasts on the surface of titanium implants, improve the activity of alkaline phosphatase, and improve the expression of osteogenic genes, thus increasing the amount of bone formation and enhancing the strength of implant-bone integration. Most elements have multiple properties, and the combined application of two or more elements can yield more biological properties than a single element. Since there are many trace elements in the human body, there is still a wide research space available in the field of the surface modification of dental implants by trace elements.